Targeted Treatment Trastuzumab is found to greatly Improve Long Term Survival of HER2 Breast Cancer Patients - Mamdouh Ramadan; Mohamed El-Wakil; Shahera Shaaban (Egyptian Journal of Medical Research, 2020)
The goal of this study is to assess the importance of adding adjuvant TRASTUZUMAB as a standard in her2 overexpressed breast cancer. Fifty female patients have known to be HER2 overexpressed breast cancer, recruited from the clinical oncology clinic at Beni-Suef University Hospital, and from the insurance hospital at Beni-Suef city. This is a retrospective study. This study was done within six months. The results of this trial indicate that one year of adjuvant trastuzumab should be considered a standard on completion of locoregional therapy and neoadjuvant or adjuvant chemotherapy. That study indicated that adding trastuzumab to chemotherapy had improved overall survival &disease free survival, all the recruited patients in that study were still alive till the end of the study and about 8% (n=4) vs 92% (n=46)  of patients developed distant recurrences. Receiving adjuvant TRASTUZUMAB for 1year without delaying in initiation (≤ 6 months) after diagnosis, offers  dramatic effects on overall survival OS and disease free survival DFS.